(untitled) - OMS (Genève, Suisse, 1998)
The book provides guidance for countries wishing to establish natioanl programmes for essential drugs, and includes discussion of quality assurance, essential drug studies, drug information and eductional activities, and research and development. In the light of increasing resistance to antimicrobials, particular attention is drawn to the need for use of reserve antimicrobials. It also presents the tenth revised model list, together with details of changes that have been made, a glossary of terms and a alphabetical list of all the drugs included
Keywords: drug resistance, microbial,essetial drugs - standards,guidelines,national health program - organization and administration